The Facts on File dictionary of marine science - Charton, Barbara; Facts on File, Inc. (New York : Facts on File, 2008)
Defines terms dealing with water chemistry, marine ecology, currents, and oceanography, and identifies scientific organizations and concepts associated with the study of the oceans.
Previous ed.: The Facts on File dictionary of marine science / [edited by] Barbara Charton.
Includes bibliographical references (p. 463-468).
Keywords: Marine sciences -- Dictionaries